Law No. 99 of the Year 2018 on Increasing the Pensions and Amending Some Provisions Of the Law on the Rights of the People with Disabilities Promulgated by law no. 10 of the year 2018 = قانون رقم 99 لسنة 2018 بشأن زيادة المعاشات وتعديل بعض أحكام قانون حقوق الأشخاص ذوى الإعاقة الصادر بالقانون رقم 10 لسنة 2018 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic